A Scientometric Review and Analysis of Studies on the Barriers and Challenges of Sustainable Construction - Hoda Alsadat Vaghefi-Rezaee; Hadi Sarvari; Setareh Khademi-Adel; David J. Edwards; Chris J. Roberts (Buildings)
Despite numerous concerns about climate change and the deterioration of nature, the construction industry is still one of the largest consumers of minerals and natural resources. In recent decades, sustainable construction using renewable and recyclable materials, reducing energy, and the adoption of more green technologies with the aim of reducing harmful impacts on the environment have received profound worldwide attention. The more key stakeholders involved strive to achieve sustainability, the more barriers they may face, which requires investigating them to have an effective plan to recognize, prevent, and control them. This paper reviews, classifies, and analyzes the major barriers of sustainable construction between January 2000 and April 2023. In this scientometric study, 153 articles were selected from the Web of Science database. Then, bibliometrics, the creation of maps from network data, as well as the illustration and exploration of those maps were conducted with the HistCite 12.03.1 and VOSviewer 1.6.20 software programs. The analytical results showed that the most profound barriers of sustainable construction are classified into 12 groups: price, economic parameters, awareness, technical, policy and regulations, design, management and government, environmental, social, materials, planning, and market.